(untitled) (Journal of Plant Disease Sciences, 2023)
Cotton ( spp.) is one of the ancient and most important Gossypium commercial crops next only to food grains and is the principal raw material for a flourishing textile industry. Despite the promising scenario in cotton, several factors are responsible for reduction in yield and quality deterioration of cotton in India. Diseases form a vital factor, the low productivity of cotton in Karnataka is attributed to many factors, one of which is the losses due to diseases, although insect pests continue to be a major production constraint. But, a large number of fungal, bacterial, viral and nematode diseases have been reported on cotton crop right from early stage to maturity. Keeping this in view, an intensive roving survey was carried out during 2022-23 to assess the severity of major foliar diseases of cotton in parts of Bt Northern Karnataka. Survey results revealed that, blight severity (32.62 Alternaria %) was more in all the regions, followed by (21.28 %) and low severity Cercospora was observed in case of bacterial blight disease(7.04%).